Genotoxic and mutagenic effects of polluted surface water in the midwestern region of Brazil using animal and plant bioassays - Rosa Dourado, Priscila Leocadia; Rocha, Monyque Palagano da; Roveda, Liriana Mara; Raposo Junior, Jorge Luiz; Candido, Liliam Silvia; Lima Cardoso, Claudia Andrea; Marin Morales, Maria Aparecida [UNESP]; Pires de Oliveira, Kelly Mari; Grisolia, Alexeia Barufatti (Soc Brasil Genetica, 2017)
This study aimed to evaluate DNA damage in animal and plant cells exposed to water from the Agua Boa stream (Dourados, Mato Grosso do Sul, Brazil) by using bioassays, and to identify the chemical compounds in the water to determine the water quality in the area. Through the cytotoxicity bioassay with Allium cepa, using micronucleus test, and comet assay, using Astyanax altiparanae fish, the results indicated that biological samples were genetically altered. Micronuclei were observed in erythrocytes of A. altiparanae after exposure to water from locations close to industrial waste discharge. The highest DNA damage observed with the comet assay in fish occurred with the exposure to water from locations where the presence of metals (Cu, Pb, Cd, Ni) was high, indicating the possibility of genotoxic effects of these compounds. Thus, these results reinforce the importance of conducting genotoxicity tests for developing management plans to improve water quality, and indicate the need for waste management before domestic and industrial effluents are released into the rivers and streams.
Keywords: Allium cepa; Astyanax altiparanae; mutagenicity; cytotoxicity; genotoxicity